HMIP prisoner survey: adults in England and Wales, 2000-2022: special licence access (UK Data Service, 2023)
The HMIP (His Majesty's Inspectorate of Prisons) Prisoner Surveys (also formerly known as Detainee Surveys) are part of the Inspectorate's duties to inspect prisons. Surveys of prisoners have been carried out systematically since 2000 at institutions being inspected, to gain important insight into detainees' experiences of offender management whilst in custody. Prisoners are issued with the survey questionnaire to return to the HMIP team, which processes the data to inform inspections of individual institutions and the HMIP annual reports. The survey is grouped into topics/themes of questions with response categories, as well as providing space for prisoners to add additional comments (such text comments are not included in these datasets). The specific objectives of the HMIP Prisoner Survey series are as follows: to produce data that are comparable as possible over time and between custodial institutions; to provide data for a large and representative sample of adult prisoners in England and Wales. So far, over 20 years' worth of data has been collected. The survey was not conducted in 2020/21 due to HMIP COVID-19 restrictions.